Analisis Aspek Hukum dalam Studi Kelayakan Suatu Bisnis (Studi Kasus: Usaha Food and Beverage Chicken Crush) - Fajri, Ridho Laksamana; Wirayuda, Fatah; Sitorus, Mhd Gifari; Annisa, Mutiara; Sihotang, Mutiah Khaira; Alfikri, Muhammad Nabil; Ramadhi, Ade Wahyu (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In an increasingly competitive era of globalization, business actors are required to be more selective in starting their business. One important step that must be taken is to conduct a business feasibility study, which covers various aspects, including market, technical, financial, management, and legal. The legal aspect is the main foundation that must be considered to ensure the continuity of business operations legally and avoid potential problems in the future. Consumer demand for quality food and beverage products is increasing, creating great opportunities for business actors. Chicken Crush, as a chicken-based culinary business, faces legal challenges ranging from business licensing to compliance with food safety standards. A business feasibility study is an important instrument in identifying crucial aspects that need to be considered. This article aims to analyze the legal aspects in a business feasibility study with a focus on the Chicken Crush case, and to show how legal compliance can be one of the keys to the success of a food and beverage business in Indonesia. Through a comprehensive analysis, it is hoped that this article can be a reference for other business actors in understanding the importance of the legal aspect, especially in the context of a food and beverage business that has special regulations.